In vitro anticoagulant activity of crude fibrinolytic protease HSFT-2 as an alternative anticoagulant agent - Afriansyah, Muhammad Ardi; Rahajoe, Toeti; Pranindira, Raksi (Universitas Nahdlatul Ulama Surabaya, 2025)
Thrombotic disorders are one of the leading causes of death in cardiovascular patients and contribute to the incidence of non-infectious diseases. The search for new anticoagulant agents to overcome the limitations associated with existing anticoagulant therapies is increasing, especially those derived from natural and microbial sources. Staphylococcus hominis HSFT-2 is a Gram-positive coccus isolated from rusip Holothutia scabra commonly known as sand sea cucumber. Fibrinolytic protease HSFT-2 has been reported to be able to degrading fibrin, which has shown several characteristics of fibrinolytic and clot-lysis activities. This study aims to evaluate the anticoagulant activity of crude fibrinolytic protease HSFT-2 in vitro as potential alternative anticoagulant agents. The research design was completely randomized, with a sample size of 21 participants calculated using the Federer formula. The material used was crude protease derived from S. hominis cultured in Skim Milk Broth. Various tests, including blood routine tests, platelet aggregation tests, and blood smear evaluations, were conducted to assess its effectiveness as an anticoagulant. Whole blood samples were divided into three groups: a positive control, a negative control, and a group treated directly with 100 µL of crude fibrinolytic protease. The normality of the data was evaluated using the Kruskal-Wallis test, while differences between groups were analyzed with one-way ANOVA. The one-way ANOVA results from the blood routine tests indicated a significant difference between the control and the fibrinolytic protease HSFT-2 (p<0.05). The platelet aggregation percentage decreased from 75.85% in the control group to 21.75% with the addition of crude protease HSFT-2. Furthermore, the blood smear evaluations revealed no abnormalities in cell formation when HSFT-2 protease was used, compared to samples without the addition of EDTA anticoagulant. In conclusion, the fibrinolytic protease HSFT-2 exhibits anticoagulant activity; however, it does not yet meet the standards required for use as an anticoagulant in routine blood tests. Future work should focus on the purification and characterization of the protease to enhance its anticoagulant potential for laboratory diagnostic applications.